Adult education programmes for rural transformation in Delta state - Abey-Fashae, G. C.; Adekoya, S. A. (Journal of Research in Adult and Continuing Education, 2023)
This study aimed at assessing adult education programmes for rural transformation in Delta State. To enable the study to achieve its objectives, five (5) research questions were raised. The study adopted a descriptive survey research design. The population of this study comprised all the people living in all communities under Patani Local Government of Delta State from which a total of two hundred (200) respondents were selected to form the sample size for the study. A questionnaire titled Questionnaire on adult education programmes for rural transformation in Delta State was the instrument used for data collection. The validity of the instrument was ascertained through the expert judgment approach while the test re-test method of estimating reliability was used to determine the reliability of the instrument. A reliability index of 0.76 was obtained using Person Product Moment Correlation Statistics. Collected data were analyzed using frequency count, simple percentage, and mean score analysis. Findings from the study revealed that the adult education programmes available in the area under study are literacy programmes, women empowerment/training programmes, health programmes, empowerment training programmes, and Family life education Programmes. In addition, it was discovered that Adult education programmes have transformed the area under study economically by helping to provide job opportunities for people in the community; encouraging education in the community by providing people with grants and scholarship opportunities; encouraging skills acquisition and capacity building for the people, provide support for people’s new economic innovations in the community as well as encourage youth involvement in trading activities in the community.